Table of Content - - (Journal of Curriculum and Teaching Methodology, 2024)
Table of Content: 1. Analyzing Biology Books Content in Shades of Sustainable Development Dimensions Mrs. Hind Mohammed Al-Maamary, Dr. Tahani Abdul Rahman Al-Muzainy 2. Identify the effectiveness of a training program based on remote supervision in developing some of the electronic supervision competencies it among the educational supervisors in the kindergarten stage in the city of Makkah Asst-Prof. Ohood Khaled Al-Saigh, Co-Prof. Hoda Muhammad Babtain 3. The effectiveness of teaching supported by illuminations in acquiring the concepts of analytic geometry among the tenth grade student and their motivation towards learning mathematics Mr. Hamed Abdullah Ali Alrudaini, Prof. Adnan Saleem Al-Abed 4. The Role of Using Micro-Leaning Strategy through Instagram to Develop Lifelong Learning Skills for Adults Ms. Wed Khaled Alshafei, Ms. Anwar Wahid Fathi, Dr. Amjaad Tariq Mujallid 5. Self-Regulated Learning Skill Levels Among 12th Grade (General Diploma) Students in the Sultanate of Oman Mrs. Salama Saif Hamed Al-Siyabi 6. Theories, practices, and challenges of teaching and learning Arabic as a modern language at the secondary stage in Dubai Dr. Nour Atta Abu Ateyh